0331 Prolonged perceived stress and saliva cortisol in a large cohort of danish public service employees: cross-sectional and longitudinal associations. (21st August 2017) - Mikkelsen, Sigurd; Forman, Julie Lyng; Fink, Samuel; Vammen, Marianne Agergaard; Thomsen, Jane Frølund; Grynderup, Matias Brødsgaard; Hansen, Åse Marie; Kaerlev, Linda; Kolstad, Henrik Albert; Reiner, Rugulies; Bonde, Jens Peter
Abstract : Objectives: The effects of prolonged stress on cortisol secretion is uncertain. This study examines the cross-sectional and longitudinal associations between prolonged perceived stress and salivary cortisol. Methods: In 2007, 4, 467 Danish public service employees participated in a study of stress and mental health, and 3, 217 participated in a follow-up in 2009. Perceived stress during the past four weeks was assessed by Cohen's four item Perceived Stress Scale. Participants were asked to collect saliva 30 minutes after awakening and at approximately 20:00 in the evening. The cortisol dependence on perceived stress was examined in regression analyses adjusted for effects of potential confounders. We adjusted for a large variation in saliva sampling times by modelling the time trajectory of cortisol concentrations in the morning and in the evening and examined if they were influenced by perceived stress. Results: Perceived stress had no statistically significant effects on the level or time trajectory of morning or evening cortisol, neither cross-sectionally nor longitudinally. The one month prevalence of frequently perceived stress was low, approximately 2.5%. Conclusions: Our results did not support the hypothesis that prolonged perceived stress is associated with the level or time trajectory of morning or evening salivary cortisol.